Konsep Kesejahteraan Perspektif Islam: Studi Para Pedagang di Pasar Raya Mekongga Kabupaten Kolaka - Marunta, Ristiyanti Ahmadul; Sari, Sarni Handayani Puspita; Nur, Abustan; Ramadhan, Ryan; Putri, Zalsyakillah Amalia (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Welfare from an Islamic perspective is the achievement of syara' goals (maqasid sharia). The maintenance of syara' aims is to protect religion (al-din), soul (al-nafs), reason (al-'aql), property (al-mal) and offspring (al-nasl). In achieving the goals of maqasid sharia, it still pays attention to sharia principles, namely the principle of monotheism, the principle of honesty, the principle of trust, the principle of justice and freedom from usury. The purpose of this research is to understand in depth the concept of welfare from an Islamic perspective of the study of traders at Pasar Raya Mekongga using qualitative research, namely looking for meaning, understanding and understanding of a phenomenon, events in human life by being involved directly or indirectly with the setting to be studied, contextual and comprehensive. This study involved traders in Mekongga Raya Market as respondents and were Muslim. The findings of this study are the concept of welfare for traders both physically and mentally, namely the achievement of material and non-material needs while still holding fast to Divine rules in all their life activities. The material obtained is money and capital, while the non-material obtained is moral and spiritual values. The conclusion is that materially and spiritually the traders believe that sustenance from Allah is always abundant so that they are able to maintain the goals of syara (Maqasid Sharia) and ensure the welfare of traders. Keywords: Welfare from an Islamic perspective, Maqasid Sharia, Moral Values, Spiritual Values.